Associations between adverse childhood experiences and weight, weight control behaviors and quality of life in Veterans seeking weight management services. (January 2021) - Masheb, Robin M.; Sala, Margaret; Marsh, Alison G.; Snow, Jennifer L.; Kutz, Amanda M.; Ruser, Christopher B.
Abstract: Introduction: A neglected area of trauma research with Veterans is the study of Adverse Childhood Experiences (ACEs). The present study aimed to examine the prevalence of ACEs, and to explore relationships between ACEs and measures of weight, eating behaviors and quality of life in weight loss seeking Veterans. Methods: Participants were 191 Veterans [mean age 58.9 ( SD  = 12.8), mean Body Mass Index (BMI) 35.4 ( SD  = 6.1), 86.9% male, 33.7% racial/ethnic minority] receiving care at VA Connecticut Healthcare System (VA CT) who attended an orientation session of VA's behavioral weight management program. Participants completed a measure of ACEs and measures related to weight, eating and health. Results: Among completers, 68.6% endorsed at least one ACE. The average number of reported ACEs was 2.2 (SD = 2.5), with 48.7% of Veterans reporting more than one type of ACE. Women were more likely to report any ACE (88.0% vs. 65.6%, p  = .025) and reported significantly more ACEs compared to males (4.2 vs. 1.9, p  < .001). ACEs were associated with lower physical activity ( p  = .05), lower quality of life ( p's  < 0.05), and lower weight-related quality of life ( p  < .01), but not weight, weight control strategies, binge eating, or alcohol use. Conclusion: ACEs are common among weight loss seeking Veterans, particularly among female Veterans. Findings suggest that there is a high rate of ACEs in Veterans, which are associated with exercise and quality of life outcomes, but not diet and weight outcomes. Highlights: Adverse Childhood Experiences (ACEs) were common among weight-loss seeking Veterans. Women Veterans reported significantly more ACEs than male Veterans. ACEs were related to physical activity, but not BMI, which has clinical implications for weight management intervention.